Synthesis of Cu2+ Doped ZnO by the Combination of Sol-Gel-Sonochemical Methods with Duck Egg Albumen as Additive for Photocatalytic Degradation of Methyl Orange - Sherly Kasuma Warda Ningsih; Hary Sanjaya; Bahrizal Bahrizal; Edi Nasra; Syuhada Yurnas (Indonesian Journal of Chemistry, 2021)
Cu2+ doped ZnO by green synthesis was successfully prepared by using a combination of the Sol-Gel-Sonochemical method. Duck egg albumen was used as an additive, a substitute for chemical additives, such as monoethanolamine (MEA) and diethanolamine (DEA). Zn(CH3COO)2·2H2O was used as a precursor, Cu(CH3COO)2·H2O was used as a dopant source with concentrations of 5 wt.%, and isopropanol was used as the solvent. The addition of albumen variations was 10, 20, 30, 40, and 50 mL. The prepared catalyst was applied for the degradation of the methyl orange dyes by using photosonolysis with variations of the degradation time of methyl orange for 30, 60, 90, 120, 150, 180, and 240 min. FTIR spectra showed stretching at 400–550 cm–1 indicating the presence of Zn–O and Zn–O–Cu metal oxides. The optimum bandgap energy value was 2.82 eV with the addition of 30 mL of albumen. XRD analysis showed the optimum particle size of 16.62–53.21 nm after adding 30 mL of additives. The SEM image showed a spherical shape with an average diameter of 2.7 μm. The optimum percentage of degradation obtained was 94.88%, with the irradiation time under UV light for 210 min.